Concept of quality of life in health care research: a review - Kaur, Mandeep; Kaur, Sukhpal (International Journal Of Community Medicine And Public Health, 2023)
Quality of life (QoL) is the most studied concept in health care research. With an increase in life expectancy and consequently with more prevalence of chronic diseases, the QOL needs to be paid attention. It is a multifactorial concept and many tools are adopted to study QOL. The present article analyses the concept of QOL in the context of healthcare research. Articles for this were searched from PubMed, CINAHAL, Cochran and EBSCO. A detailed review of QoL in health care research including its components, models and various tools being used with their application are discussed in the current article.